Savage Dreams : a Journey into the Hidden Wars of the American West. - Solnit, Rebecca (University of California Press, 2014)
""A beautiful, absorbing, tragic book.""--Larry McMurtryIn 1851, a war began in what would become Yosemite National Park, a war against the Indigenous inhabitants. A century later-in 1951-and a hundred and fifty miles away, another war began when the U.S. government started setting off nuclear bombs at the Nevada Test Site. It was called a nuclear testing program, but functioned as a war against the land and people of the Great Basin. In this foundational book of landscape theory and environmental thinking, Rebecca Solnit explores our national Eden and Armageddon and offers a pathbreaking histor